A randomized controlled trial of cognitive remediation for a national cohort of forensic patients with schizophrenia or schizoaffective disorder - Corvin, Aiden; Kennedy, Harry (My University, 2019)
Background: Evidence is accumulating that Cognitive Remediation Training (CRT) is effective for ameliorating cognitive deficits experienced by patients with schizophrenia and accompanying functional impairment. There has been no randomized controlled trial of CRT using a nationally representative population of forensic patients, despite the significant cognitive deficits frequently present within this group. Methods: Sixty-five patients with schizophrenia or schizoaffective disorder were enrolled in a single blind randomized controlled trial of CRT versus treatment as usual (TAU); representing 94% of those eligible within a national forensic cohort. The primary outcome measure was the composite score of the MATRICS Consensus Cognitive Battery (MCCB). Secondary outcome measures included neurocognitive and social cognitive domains, symptoms, and ‘real world’ functioning. Patient satisfaction was examined using an exit interview. Participants were reassessed at 8 months follow up. All data were analyzed using an intention to treat design (ITT). Results: For the primary outcome measure, the MCCB composite score, there were significant differences between those who participated in CRT and those receiving TAU at both end of treatment and 8 months follow up (Cohen’s d = 0.34. Significant improvements were observed in visual and working memory. Mediation analysis found that those who cognitively benefited from CRT had corresponding improved functioning, and more net positive therapeutic moves i.e. moves to units with lower security within the hospital. Ninety-six percent believed their cognitive gains positively affected their daily lives. Conclusions: CRT may be an acceptable and efficacious intervention for forensic patients with schizophrenia or schizoaffective disorder.
PUBLISHED
Keywords: Schizophrenia; Forensic mental health; Cognitive remediation training (CRT); Neurocognition; Effectiveness; Clinical trial